The Right of People with Disabilities to Health: What Is Expressed by the Architectonics of Legislation? - Ingrida Baranauskienė (Social Welfare: Interdisciplinary Approach)
The article formulates the research problem: what ideas dominate in architectonics of two laws under scientific analysis (The Human Right to Health of the World Health Organization, Article 12, and parts of the Law on the Health System of the Republic of Lithuania related to the situation of people with disabilities in the healthcare system)? The research methodology is grounded on the ideas of postpositivism and ethnographic approach. The thematic analysis has been chosen as a method of data processing. The findings allow formulating a conclusion that architectonics of legislations of the World Health Organization has a clear jurisprudential foundation; whereas the Law on the Health System of the Republic of Lithuania provides preconditions for various stipulations, which results in people with disabilities facing manifestations of discrimination in Lithuanian system of health care.